Upaya dari Segi Pendekatan Makro untuk Mengatasi Kecanduan Judi Online di Kalangan Mahasiswa - Dyana, Multynisari Dyana Putri; Nuryanti, Lusi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Technological developments and economic factors have increased the prevalence of online gambling among college students, negatively impacting their mental health, finances, and academic performance. This phenomenon requires serious attention for effective prevention and management. Objectives: This study aims to determine the impact of online gambling on college students and design a holistic and sustainable intervention based on Bronfenbrenner's theory. The scope of the study includes causal factors, psychological and financial impacts, and intervention measures that can be implemented in college and family environments. Methods: The methods used include literature review and qualitative analysis of various data sources, including journals, case reports, and policy documents. Results: The results indicate that online gambling causes financial losses, mental disorders such as stress and depression, and decreased academic performance in students. The proposed interventions include education, counseling, group support, and synergy between families and educational institutions. Conclusion: The conclusions of this study emphasize the importance of collaborative, multi-stakeholder-based preventive and rehabilitative measures to reduce the negative impacts of online gambling and improve students' awareness and mental health. Keywords: Online gambling, Psychological impact, Bronfrenbener's theory